2021
DOI: 10.5267/j.msl.2020.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge sharing, trust as mediation on servant leadership and job performance

Abstract: This study analyzes the effect of servant leadership on job performance with, trust and knowledge sharing as mediating variables. The research is classified in the quantitative analysis used to test the significance between latent variables. The study sample includes 164 of the STIE Malangkucecwara postgraduate program alumni from 2010 to 2019. Data are collected through an online questionnaire and the SmartPls processes the results. The results show that job performance was directly affected by servant leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 1 publication
1
6
0
2
Order By: Relevance
“…The positive relationship between LSs and IEP supports the results of research conducted by (Megawaty et al 2022;Tran and Truong 2021;Alahbabi et al 2021;Wanta and Augustine 2021;Pratiwi and Nawangsari 2021;Kaltiainen and Hakanen 2022;Peng and Chen 2021;Kadarusman and Bunyamin 2021;Ahmed et al 2022;Ali et al 2018;Humborstad et al 2014;Qian et al 2018;Kim et al 2018;Fu et al 2020;Shi et al 2022;Cheong et al 2019). The positive relationship between LSs and HIHRMPs strengthens the results of the research conducted by (Demo et al 2022;Zhao and Huang 2022;Kloutsiniotis et al 2022;AlAbri et al 2022).…”
Section: Theoretical Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…The positive relationship between LSs and IEP supports the results of research conducted by (Megawaty et al 2022;Tran and Truong 2021;Alahbabi et al 2021;Wanta and Augustine 2021;Pratiwi and Nawangsari 2021;Kaltiainen and Hakanen 2022;Peng and Chen 2021;Kadarusman and Bunyamin 2021;Ahmed et al 2022;Ali et al 2018;Humborstad et al 2014;Qian et al 2018;Kim et al 2018;Fu et al 2020;Shi et al 2022;Cheong et al 2019). The positive relationship between LSs and HIHRMPs strengthens the results of the research conducted by (Demo et al 2022;Zhao and Huang 2022;Kloutsiniotis et al 2022;AlAbri et al 2022).…”
Section: Theoretical Implicationssupporting
confidence: 77%
“…Recent research results show that servant leadership relates to IEP and affects employee motivation (Tran and Truong 2021), job performance (Alahbabi et al 2021), and employee performance (Wanta and Augustine 2021;Pratiwi and Nawangsari 2021). This relationship can indirectly occur, for example, servant leadership and task performance are mediated by work engagement (Kaltiainen and Hakanen 2022;Peng and Chen 2021), and servant leadership and job performance by trust and knowledge sharing (Kadarusman and Bunyamin 2021). Shared leadership relates to employee performance (Ahmed et al 2022;Ali et al 2018) and individual performance (Humborstad et al 2014).…”
Section: Lss and Iepmentioning
confidence: 99%
“…POS, which can be interpreted as employees' perceptions of organizational care and appreciation for their contributions (Eisenberger et al 1986), had been proven to have a positive effect on knowledge sharing (Cugueró-Escofet et al 2019). On the other hand, servant leadership as a context for more minor interactions was also confirmed to positively affect knowledge sharing (Kadarusman & Bunyamin 2021, Tripathi et al 2020). Besides, previous research showed the role of organizational citizenship behavior (OCB) in the relationship between POS, servant leadership, and knowledge sharing.…”
Section: Introductionmentioning
confidence: 92%
“…However, despite the continuous call for an underlying process via which CER perceptions influence millennials' job-seeking intentions, little research has empirically examined the role of psychological factors in the above relationship [1,2]. Furthermore, while many researchers have focused on the effects of organizational trust on existing employees' performance and commitment (e.g., [3,4]), trust research on job-seeking literature for prospective employees is very limited. This suggests that the impacts of organizational trust are largely applicable to existing employees of an organization, leaving an important gap in the literature.…”
Section: Introductionmentioning
confidence: 99%